Across Seas and Cultures: The Hajj Journeys of Sulu Muslims and Their Malay World Parallels - Abadi, Mansurni; Pratiwi, Nia Nur; Golasila, Ana Octavia (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
This research explores the maritime Hajj journeys of Sulu Muslims and their connection to the cultural and religious dynamics of the broader Malay world. The maritime pilgrimage, especially within the context of Sulu Muslims, remains largely underexplored in existing literature, highlighting a significant research gap in understanding Muslim-minority religious practices. This study aims to address this gap by examining how the maritime Hajj journey impacts Sulu Muslims, a minority in a Catholic-majority country, and their Malay counterparts. Using a qualitative approach, primary sources such as oral histories from pilgrims and archival records uncover the cultural, religious, and social dimensions of these journeys. The research highlights key themes such as the challenges of maritime travel, the role of religious networks, and cultural exchanges during the pilgrimage. The findings reveal that the Hajj not only fulfills a religious duty but also fosters cross-regional identity and solidarity among Muslims in the Sulu Archipelago and Southeast Asia. The study concludes that the Hajj serves as both a spiritual endeavor and a platform for cultural continuity and interregional unity, influencing societal transformation. By capturing these aspects, the research aims to enrich understanding of the Hajj as a multifaceted phenomenon, emphasizing the enduring significance of maritime routes in shaping Southeast Asia’s religious and cultural landscapes.